Creating a Space for Tribal Sahariya Youth to Improve Access to Safe Water in Rural Rajasthan, India - Sisodia, Renu (Auckland University of Technology, 2024)
Access to safe water is a fundamental human right, yet Indigenous communities, such as the Sahariya in Rajasthan, India, face significant challenges in securing this vital resource. This study examines the obstacles encountered by the Sahariya, classified as a scheduled tribe in India, within the context of the global water crisis, exacerbated by pollution, inadequate governance, and climate change. Despite Government of India initiatives like the Jal Jeevan Mission (JJM), aimed at enhancing rural water supply, challenges persist, particularly in reaching remote tribal communities. The Sahariya community’s struggle to access safe and reliable water is compounded by systemic discrimination based on caste, gender, and ethnicity. Government schemes frequently disproportionately benefit upper castes, resulting in inequitable access to water resources. This disparity significantly impacts Sahariya women and girls, who bear the burden of travelling long distances to collect water, impeding their well-being, education and economic opportunities. Historical displacements due to colonial and post-independence policies have further exacerbated these issues, with structural discrimination persisting despite policy attempts at equity. Grounded in a critical research paradigm and employing participatory action research (PAR) as the methodology, this study explores the water access challenges faced by the Sahariya. It provides a platform for Sahariya youth to propose solutions. Influenced by critical theory, critical reflexivity, and an anti-oppressive approach rooted in social work practice, the study engaged 48 Sahariya youth participants. Participatory videos, focus group discussions (FGDs), resource mapping, and transect walks were utilised as data collection methods. Data analysis was conducted using a participatory data analysis approach, with participants contributing to the creation of a short film (https://youtu.be/AODuocliBOs) to raise awareness about their plight. The findings revealed three primary strategies advocated by the Sahariya youth for positive change: community mobilisation, the formation of associations (Sangathan), and the creation of a film for awareness. This research enhances the understanding of the Sahariya’s struggle for safe water access and advocates for their right to equitable water distribution. The study demonstrates the usefulness of participatory research in fostering community engagement, building capacity, and amplifying the voices of marginalised groups such as the Sahariya youth. By providing comprehensive training and technical support and fostering strategic partnerships with non-government organisations (NGOs) and policymakers for effective advocacy, participatory video can be a powerful tool for driving substantive social change. The research underscores the necessity for inclusive and equitable policies that address entrenched structural discrimination within current water management systems. It stresses the importance of authentic, non-tokenistic participation, urging the government to recognise the rights of the Sahariya and implement equity-based and rights-based approaches to improve access to safe water. Furthermore, it highlights the need to avoid placing the burden of creating water resources on marginalised communities. Instead, the study calls for robust support from the government, NGOs, and other stakeholders to provide the necessary resources and infrastructure to ensure sustainable water access. The implications are profound, advocating for a framework that prioritises the voices of the most affected communities, such as the Sahariya tribe, ensuring their needs and perspectives are represented in policy and practice.
Keywords: Sahariya tribe; water; rural India; participatory action research; participatory video; youth